2019
DOI: 10.1353/hpu.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medicaid Access in Times of Health Policy Change: Solutions from Focus Groups with Frontline Enrollment Workers

Abstract: Enrollment navigators and government-employed Medicaid workers were an important element in the Affordable Care Act's (ACA) initial enrollment success. The Centers for Medicare and Medicaid Services eliminated 41% of funding for 2017 navigator programs and 90% of funding for outreach, arguing less investment was needed. Given that many remain uninsured, it is critical to identify effective enrollment practices. This study characterizes barriers and enrollment strategies from the perspective of California's Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Most of the studies identified [16][17][18][19][20][21][22] individual assistance as a key strategy used by healthcare providers and community-based organizations to help people enroll for health insurance. The terminology used to describe individual assistance varied.…”
Section: Individual Assistancementioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies identified [16][17][18][19][20][21][22] individual assistance as a key strategy used by healthcare providers and community-based organizations to help people enroll for health insurance. The terminology used to describe individual assistance varied.…”
Section: Individual Assistancementioning
confidence: 99%
“…Some FQHCs and community-based organizations had assistance programs prior to the implementation of the ACA. These organizations expanded their capacity to help more people once the ACA coverage expansion took effect by hiring more assisters [17][18][19][20][21][22]. Other organizations such as The Weill Cornell Community Clinic (WCCC) utilized their licensed social worker to screen patients for coverage eligibility and collaborated with another community organization to help their patients complete the enrollment process [18].…”
Section: Individual Assistancementioning
confidence: 99%
See 3 more Smart Citations